2015
DOI: 10.1111/jvim.13571
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Patterns in Urinary Tract Infections in Dogs (2010–2013)

Abstract: BackgroundUrinary tract infections (UTIs) are common in dogs. The responsible bacterial populations have evolved with increasing resistance to many antimicrobials.ObjectiveTo characterize the antimicrobial susceptibility patterns of canine urinary tract isolates over a 51‐month period.AnimalsOne thousand six hundred and thirty‐six bacterial isolates from 1,028 dogs.MethodsAerobic bacterial isolate growth and susceptibility data from urine cultures of dogs were identified, retrospectively. Medical records were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
123
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(153 citation statements)
references
References 30 publications
23
123
6
1
Order By: Relevance
“…These findings are in agreement with the observation that UTIs in dogs are generally caused by a single bacterial species, the predominant being E. coli. 15 Several recent studies on UTI in dogs in temperate countries [6][7][8][9] have shown that E. coli is the predominant cause of UTI as seen in the present study and our previous study for the period of 2004-2009 in Grenada. 10 UTI is more common in female dogs, which is in agreement with the results of the previous study in Grenada.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These findings are in agreement with the observation that UTIs in dogs are generally caused by a single bacterial species, the predominant being E. coli. 15 Several recent studies on UTI in dogs in temperate countries [6][7][8][9] have shown that E. coli is the predominant cause of UTI as seen in the present study and our previous study for the period of 2004-2009 in Grenada. 10 UTI is more common in female dogs, which is in agreement with the results of the previous study in Grenada.…”
Section: Discussionsupporting
confidence: 65%
“…5 In a study in the U.S, over 80% of urinary tract isolates were found to be susceptible to enrofloxacin. 5 Despite several recent publications on bacterial UTI in dogs from Europe and the United States, [6][7][8][9] there is scanty information from tropical areas. The results of a study on the canine urine samples from cases suspected of UTI in Grenada, a tropical Caribbean island nation during the period of 2004 to 2009 were published recently by Hariharan et al 10 E. coli was the predominant species associated with UTI, followed by Proteus mirabilis and Staphylococcus intermedius/Staphylococcus pseudintermedius.…”
Section: Urinary Tract Infections (Uti) Are the Most Common Cause Of mentioning
confidence: 99%
“…Drugresistant pathogens have been documented in animals as they have in humans. For example, Wong et al reported on susceptibility of bacterial pathogens causing urinary tract infections in dogs with data collected between 2010 and 2013 [17]. Multidrug-resistant E. coli strains were found more commonly in complicated UTI than in uncomplicated cases.…”
Section: So the Million Dollar Question Remains "Does The Use Of Antmentioning
confidence: 99%
“…Many reports have shown that bacterial UTI are more common in older female dogs, indicating that this is an important risk factor (Kivisto et al, 1977;Bush et al, 1978;Thomsen et al, 1986;Cavana et al, 2008;Sidjabat et al, 2009;Hall et al, 2013;Wong et al, 2015). The mean age at diagnosis regardless of sex is approximately 7-8 years (Ling et al, 2001;Cohn et al, 2003).…”
Section: Epidemiology Of Canine Bacterial Urinary Tract Infectionmentioning
confidence: 99%
“…In addition, persistent and recurrent urinary tract infections are regularly diagnosed in small animal referral practice (Norris et al, 2000;Seguin et al, 2003). Norris et al (2000) suggested that recurrent or persistent UTI are present in up to 4.5% of dogs with UTI or 0.3% of the canine hospital population, and recurrent or persistent UTI was identified in 27.1% of dogs included in a recent study reporting on urinary bacterial isolates from dogs presenting to a veterinary teaching hospital (Wong et al, 2015). Whilst the conventional view has been that the majority of bacterial cystitis episodes resolve with a 7-14 day course of oral antimicrobials, it is now apparent that assumption of microbiologic cure may be ill advised.…”
Section: General Introductionmentioning
confidence: 99%